The Hydrogen Storage Properties and Catalytic Mechanism of the AZ31-WS2 Nanotube/Pd Composite - Song-Jeng Huang; Veeramanikandan Rajagopal; Sakthipriya Balu; Sivakumar Selvaraju; Murugan Subramani (Nanomaterials)
Magnesium-based alloys, known for their high hydrogen storage capacity, suffer from sluggish kinetics and high activation energy barriers. It can be further optimized through synergistic combinations with metal hydrides. This study aims to address these limitations by investigating the hydrogen sorption properties of AZ31 magnesium alloy combined with different compositions of WS2 nanotubes (NTs) and Pd. The materials AZ31, WS2 (tungsten disulfide) NTs, and Pd were pre-processed via the mechanical ball milling process. Field emission-scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM) were employed to investigate the composite morphology and confirm the nanotubular structure of WS2. This work is among the first to explore the synergistic catalytic effects of WS2 nanotubes and Pd on the hydrogenation/dehydrogenation behavior of AZ31 alloys. The composite with 8 wt.% WS2 NT/Pd demonstrated the fastest hydrogen sorption kinetics and a significant reduction in activation energy, from 123.25 kJ/mol to 104.58 kJ/mol. These results highlight the enhanced dehydrogenation performance of AZ31 through catalyst inclusion, offering a promising approach to improve hydrogen storage materials. These findings highlight the potential of combining inorganic NTs and transition metals as effective catalysts to enhance the hydrogen storage performance. This research paves the way for developing advanced hydrogen storage materials with improved performance, contributing to a sustainable energy future.